2011
DOI: 10.1016/j.ijfoodmicro.2011.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, distribution, and molecular characterization of Salmonella recovered from swine finishing herds and a slaughter facility in Santa Catarina, Brazil

Abstract: Swine can carry Salmonella strains that may be transmitted to humans by pork products. This investigation determined the distribution and types of Salmonella in 12 swine finishing herds and a slaughter facility in Santa Catarina, Brazil. A total of 1258 samples, consisting of environmental, feed, carcass, lymph node, and fecal material were collected and submitted to bacteriological isolation of Salmonella. From 487 positive samples, 1255 isolates were recovered and confirmed to be Salmonella. The distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
67
3
19

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(105 citation statements)
references
References 44 publications
13
67
3
19
Order By: Relevance
“…A Salmonella choleraesuis é a principal sorovar capaz de causar doença clínica em suínos, sendo rara nos rebanhos tecnificados do Brasil (Kich et al, 2011). Entretanto, os suínos podem se infectar com uma variedade de sorovar que não cause a doença clínica, mas que pode ser importante fonte de contaminação para os produtos finais.…”
Section: Doenças Importantes Na Segurança Alimentarunclassified
See 1 more Smart Citation
“…A Salmonella choleraesuis é a principal sorovar capaz de causar doença clínica em suínos, sendo rara nos rebanhos tecnificados do Brasil (Kich et al, 2011). Entretanto, os suínos podem se infectar com uma variedade de sorovar que não cause a doença clínica, mas que pode ser importante fonte de contaminação para os produtos finais.…”
Section: Doenças Importantes Na Segurança Alimentarunclassified
“…Entretanto, os suínos podem se infectar com uma variedade de sorovar que não cause a doença clínica, mas que pode ser importante fonte de contaminação para os produtos finais. A prevalência destas sorovares nos suínos de abate é elevada, e as mais frequentes são Typhimurium, Panamá, Senftenberg, Derby e Mbandaka (Kich et al, 2011). Como a Salmonella Typhimurium é a segunda mais importante nas infecções alimentares em humanos, deve-se enfatizar a necessidade e a importância de implementar programas de controle que englobem desde as unidades produtoras e o transporte, até o abate e o interior dos abatedouros (Lima et al, 2016).…”
Section: Doenças Importantes Na Segurança Alimentarunclassified
“…In Brazil, some studies have demonstrated an increase of multidrug-resistant (MDR) S. Typhimurium strains Bessa et al, 2007;Fernandes et al, 2009;Kich et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Despite its clinical importance, there are few studies that have molecularly characterized S. Typhimurium strains in Brazil and assessed their antimicrobial resistance profile Bessa et al, 2007;Tavechio et al, 2009;Kich et al, 2011). Therefore, the aims of this study were to assess the presence of some virulence markers and to evaluate the antimicrobial resistance patterns and the genotypic diversity using PFGE, MLVA and ERIC-PCR of S. Typhimurium strains isolated from humans and food sources between 1983 and 2013 in Brazil to better understand their pathogenic potential, resistance profile, epidemiology and genotypic diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports documented the presence of S. Enteritidis in swine abattoirs in Brazil (BESSA et al, 2004;KICH et al, 2011). Strategies used in abattoirs to prevent S. enterica growth include lower storage temperatures and surface decontamination using acids (SUN et al, 2003;PIPEK et al, 2006).…”
Section: Introductionmentioning
confidence: 99%